2010
DOI: 10.1109/tmag.2010.2045487
|View full text |Cite
|
Sign up to set email alerts
|

Grid-Enabled Tabu Search for Electromagnetic Optimization Problems

Abstract: The use of Grid Computing to solve electromagnetic optimization problems by means of the Tabu Search strategy is proposed in this paper. In order to significantly reduce the prohibitive computational cost of the numerical analyses required by the majority of iterative algorithms, two different grid-enabled Tabu Search strategies have been ported in the grid. Both strategies belong to the Domain Decomposition family: the decomposition of the search space and the decomposition of the neighborhood. The performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…In this case, the left mold radius R 1 was also optimized. The objective function value of the this optimal solution was f = 0.012, which is comparable to the known solutions from the literature [31]. Regarding the sensitivity analysis, the optimization showed that, in order to reach very low values of the error function, the value of the R 1 parameter (the radius of the g − h curve which is the arc of circumference describing the left mold) tends to be close to the maximum allowed value (13).…”
Section: Full Fea-based Optimization and Model Validationsupporting
confidence: 71%
“…In this case, the left mold radius R 1 was also optimized. The objective function value of the this optimal solution was f = 0.012, which is comparable to the known solutions from the literature [31]. Regarding the sensitivity analysis, the optimization showed that, in order to reach very low values of the error function, the value of the R 1 parameter (the radius of the g − h curve which is the arc of circumference describing the left mold) tends to be close to the maximum allowed value (13).…”
Section: Full Fea-based Optimization and Model Validationsupporting
confidence: 71%
“…Amongst researches that have used meta-heuristic algorithms in the electromagnetic area, we can point to the research of Cau et al [1] using the neural network inversion-based designed of a high field superconducting dipole. Carcangiu et al [2] have optimized electromagnetic problems by using Tabu search. Savini and Di Barba [3] have done Loney's Solenoid optimization by means of a deterministic attitude and have presented acceptable results.…”
Section: Introductionmentioning
confidence: 99%
“…Carcangiu et al [2] have optimized electromagnetic problems by using Tabu search. Savini and Di Barba [3] have done Loney's Solenoid optimization by means of a deterministic attitude and have presented acceptable results.…”
Section: Introductionmentioning
confidence: 99%